Characterizing Symptoms Before and Following Concussion in Professional Hockey. Issue 6 (November 2022) - Bruce, Jared M.; Meeuwisse, Willem; Hutchison, Michael G.; Comper, Paul; Echemendia, Ruben J.
Abstract : Objective: Examine SCAT5 baseline and acute symptom subscales in professional hockey players. Design: Longitudinal case–control. Setting: Preseason medical evaluations and suspected concussion evaluations. Participants: NHL/AHL players were given the NHL-modified SCAT5 before the 2018-2019 season (n = 1924). During the season, English-speaking players evaluated within 1 day of injury and diagnosed with concussion (n = 140) were compared with players evaluated for possible concussion, but not given a concussion diagnosis (n = 174). Independent Variables: Concussion diagnosis and demographic characteristics. Main Outcome Measures: Postconcussion Symptoms Scale (PCSS) items were subdivided into affective/emotional, cognitive, somatic/physical, sleep, and headache subscales. Results: Cognitive (13%), somatic/physical (10%), sleep (26%), affective (18%), and headache (6%) symptoms were reported by players at baseline. Concussed players reported more acute symptoms than active controls on each of the subscales (all P 's < 0.001). Players who underwent a suspected concussion evaluation were more likely to be diagnosed with concussion if they reported affective/emotional symptoms at baseline ( P < 0.001). Postinjury cognitive ( P < 0.001), somatic/physical ( P < 0.001), and headache ( P < 0.001) symptoms best differentiated concussed players and active controls. Conclusions: Player reports of increased cognitive difficulties, somatic/physical difficulties, and headache were most associated with concussion diagnosis at the acute evaluation. An abbreviated "acute" PCSS that includes only headache, cognitive, and/or physical symptoms may be useful for diagnostic purposes when evaluation time is limited. Approximately 2% of players reported significantly elevated affective/emotional symptoms at baseline and report of affective/emotional symptoms at baseline was associated with an increased likelihood of concussion diagnosis among players referred for a suspected concussion evaluation.